2005
DOI: 10.1158/1078-0432.ccr-04-2424
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of BRCA1 Status in Patients with Breast Cancer Using Estrogen Receptor and Basal Phenotype

Abstract: Purpose:To investigate the proportion of breast cancers arising in patients with germ line BRCA1 and BRCA2 mutations expressing basal markers and developing predictive tests for identification of high-risk patients. Experimental Design: Histopathologic material from182 tumors in BRCA1mutation carriers, 63 BRCA2 carriers, and 109 controls, collected as part of the international Breast Cancer Linkage Consortium were immunohistochemically stained for CK14, CK5/6, CK17, epidermal growth factor receptor (EGFR), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

44
457
1
21

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 579 publications
(525 citation statements)
references
References 28 publications
44
457
1
21
Order By: Relevance
“…As the majority of BRCA1 mutation-associated breast tumours are ER-negative (Lakhani et al, 2005), the absence of an association in our study of breast cancer with the TP53 and MDM2 SNPs in BRCA1 mutation carriers is consistent with the lack of an association with ER-negative cancers in the general population. …”
Section: Discussionsupporting
confidence: 83%
“…As the majority of BRCA1 mutation-associated breast tumours are ER-negative (Lakhani et al, 2005), the absence of an association in our study of breast cancer with the TP53 and MDM2 SNPs in BRCA1 mutation carriers is consistent with the lack of an association with ER-negative cancers in the general population. …”
Section: Discussionsupporting
confidence: 83%
“…We show that identification of basal markers (HMWCKs, c-Kit and EGFR) positivity within this group of TNBC could identify a subgroup of tumors, BLBC. It has been shown that BLBC consistently overexpress HER1 or EGFR (Nielsen et al, 2004;Lakhani et al, 2005;Masuda et al, 2005), EGFR inhibitors may have a role in the treatment of this tumor subtype. The basal markers are not consistently used in the standard histological diagnosis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This was performed simply to increase the yield of high-grade, ER-negative breast carcinomas, as these are more common in the younger age group. The majority of BRCA-1-associated tumors have the basal phenotype, 8,18,19 but the BRCA-1 status was not available for any of our cases.…”
Section: Discussionmentioning
confidence: 99%